The Effect of Fermented Lingonberry Juice on Candida glabrata Intracellular Protein Expression - Pirjo Pärnänen; Ali Nawaz; Timo Sorsa; Jukka Meurman; Pirjo Nikula-Ijäs (Hindawi Limited, 2017)
Lingonberries have a long traditional use in treating fungal infections on mucosal membranes, but very little is known about the exact antifungal mechanisms. We tested the effects of fermented lingonberry juice on Candida glabrata intracellular protein expression. A Candida glabrata clinical strain was grown in the presence of fermented lingonberry juice (FLJ). Also the effect of lowered pH was tested. Intracellular protein expression levels were analyzed by the 2D-DIGE method. Six proteins detected with ≥1.5-fold lowered expression levels from FLJ treated cells were further characterized with LC-MS/MS. Heat shock protein 9/12 and redoxin were identified with peptide coverage/scores of 68/129 and 21/26, respectively. Heat shock protein 9/12 had an oxidized methionine at position 56. We found no differences in protein expression levels at pH 3.5 compared to pH 7.6. These results demonstrate that FLJ exerts an intracellular stress response in Candida glabrata, plausibly impairing its ability to express proteins related to oxidative stress or maintaining cell wall integrity.